Mental Images of Nurses with and without Patient with COVID-19: A Metaphor Study - Müjde Moran; Firdevs Ebru Özdemir; Zahide Gül Yazgi Demir; Mualla Yilmaz (Indian Journal of Psychiatric Nursing)
Introduction: The purpose of this study is to determine the perceptions of nurses who had COVID-19 disease and recovered and who were not sick through metaphors. Materials and Methods: This study was carried out with 50 nurses who were recovered from COVID-19 disease and 50 nurses who were not sick during the pandemic process who were working as nurses in a university hospital 3 months after the first wave of pandemics started in Turkey. The study is the qualitative research, which is as data collection technique, metaphors were used. The data collection form consists of six questions containing personal information and one metaphor question. The metaphors developed by nurses regarding the “COVID-19 disease” and the common features of these metaphors were tried to be determined. The content analysis was made. Results: It was determined that the answers given by the nurses were total of 75 metaphors in seven categories. It was determined that all of the metaphorical perceptions of the nurses regarding the “COVID-19 disease” were negative metaphoric perceptions, and the meanings of the metaphors that were seen as positive metaphors such as marriage, friend, life partner, love, hope under the emotions main theme, and relationship/moods sub-theme were negative when the content was examined. Conclusion: The results show that the metaphors expressed by the nurses include pessimism and negativity. This study reflects the ideas of nurses working with all their strength during the COVID-19 pandemic and puts forth the psychological state of nurses.